Analisis Resiko Industri Kerajinan Pelepah Pisang “Pa’E Debog” di Desa Balenrejo - Lina Agustina; Deviana Diah Probowati (Politeknik Kampar, 2023)
. This study aims to determine whether the craft of silhouette painting, bags, and wallets